2012
DOI: 10.7314/apjcp.2012.13.1.395
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Adiponectin and Two Different Cancers: Breast and Colon

Abstract: Objectives: Breast and colon cancer are neoplasms well known to be related to obesity. Adiponectin, a protein that increases in obesity, seems to be involved in the relationship but clinical data are limited. Methods: In this study, we therefore evaluated the serum adiponectin levels in 87 breast and 27 colon cancer patients and assessed the relation with BMI, menopausal status, receptor status and stage of disease. Results: Serum adiponectin levels were lower in cancer cases (8583 ± 2095 ng/ml for breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Adiponectin also inhibits nuclear factor-Kβ activation, which is effective in the development of breast cancer (15). For these reasons, various studies have shown the relationship between decreased adiponectin levels and breast cancer (16,17). Although the relationship between plasma adiponectin levels and breast cancer in postmenopausal patients has been demonstrated, the relationship between adiponectin levels and cancer in premenopausal women has not been clearly displayed (18)(19)(20).…”
Section: Discussionmentioning
confidence: 95%
“…Adiponectin also inhibits nuclear factor-Kβ activation, which is effective in the development of breast cancer (15). For these reasons, various studies have shown the relationship between decreased adiponectin levels and breast cancer (16,17). Although the relationship between plasma adiponectin levels and breast cancer in postmenopausal patients has been demonstrated, the relationship between adiponectin levels and cancer in premenopausal women has not been clearly displayed (18)(19)(20).…”
Section: Discussionmentioning
confidence: 95%
“…Reduced circulatory levels of adiponectin have been shown in obese patients and implicated in the development of obesity-related malignancy (Yang et al, 2002;Cnop et al, 2003). Low ApN levels were found in breast, endometrial, prostate, colon and gastric cancers (Mantzoros et al, 2004;Ishikawa et al, 2005;Michalakis et al, 2007;Kumor et al;2009;Gonullu et al, 2010;Chen et al, 2012;Gulcelik et al, 2012;Ho et al, 2012). A positive correlation was shown between body-mass index and colorectal cancer in several studies (Murphy et al, 2000;Moore et al, 2004).…”
Section: Association Of Adiponectin Receptor (Adipo-r1/-r2) Expressiomentioning
confidence: 99%
“…Abundant evidence indicates that adiponectin suppresses the growth of cancer cells and reduces the risk of cancer (14,46). Studies have reported that serum adiponectin levels are inversely associated with RCC, and breast and colon cancer (47,48). While the preponderance of evidence suggests that an inverse association exists between adiponectin and malignancy, another study reported that higher levels of serum adiponectin were associated with RCC risk, specifically among African-American males (31).…”
Section: A B C D Ementioning
confidence: 91%